Beginning software engineering - Stephens, Rod, 1961- (John Wiley & Sons, Inc., 2022)
Discover the foundations of software engineering with this easy and intuitive guide In the newly updated second edition of Beginning Software Engineering, expert programmer and tech educator Rod Stephens delivers an instructive and intuitive introduction to the fundamentals of software engineering. In the book, you'll learn to create well-constructed software applications that meet the needs of users while developing the practical, hands-on skills needed to build robust, efficient, and reliable software. The author skips the unnecessary jargon and sticks to simple and straightforward English to help you understand the concepts and ideas discussed within. He also offers you real-world tested methods you can apply to any programming language. You'll also get: Practical tips for preparing for programming job interviews, which often include questions about software engineering practices ; A no-nonsense guide to requirements gathering, system modeling, design, implementation, testing, and debugging ; Brand-new coverage of user interface design, algorithms, and programming language choices. Beginning Software Engineering doesn't assume any experience with programming, development, or management. Its plentiful figures and graphics help to explain the foundational concepts and every chapter offers several case examples, Try It Out, and How It Works explanatory sections. For anyone interested in a new career in software development, or simply curious about the software engineering process, Beginning Software Engineering, Second Edition is the handbook you've been waiting for.